Review of innovative uses of biochar in environmental applications for nitrobenzene removal in aqueous and soil phases - Karre, Avinashkumar V.; Cai, Tianxing (Frontiers in Chemical Engineering, 2023)
Biochar has been found to be an effective material for the removal of nitrobenzene from both aqueous and soil phases. Some innovative uses of biochar in environmental applications for nitrobenzene removal include: 1) Biochar amendments for soil remediation. 2) Biochar for water treatment. 3) Biochar-based adsorbents. 4) Biochar-based membranes. Therefore, biochar is a promising material for the removal of nitrobenzene from both aqueous and soil phases, and its innovative uses in environmental applications continue to be explored. This paper presents the toxicity of nitrobenzene and potential hazards, with a discussion on the motivation and recent resolutions for nitrobenzene removal in aqueous and soil phases. Methodological cornerstones of innovative uses of biochar in environmental applications for nitrobenzene removal in aqueous and soil phases are introduced and reviewed. Overview and perspectives for the corresponding application are also provided. The innovative uses of biochar in environmental applications for nitrobenzene removal in aqueous and soil phases can bring new insights and add tremendous value to environmental chemical engineering.